2019
DOI: 10.3390/ijms20225692
|View full text |Cite
|
Sign up to set email alerts
|

Brain Susceptibility to Methyl Donor Deficiency: From Fetal Programming to Aging Outcome in Rats

Abstract: Deficiencies in methyl donors, folate, and vitamin B12 are known to lead to brain function defects. Fetal development is the most studied but data are also available for such an impact in elderly rats. To compare the functional consequences of nutritional deficiency in young versus adult rats, we monitored behavioral outcomes of cerebellum and hippocampus circuits in the offspring of deficient mother rats and in adult rats fed a deficient diet from 2 to 8 months-of-age. We present data showing that the main de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Of interest, the thickness of the EAT is a predictor of fatal and nonfatal coronary events in the general population, regardless of the traditional cardiovascular risk factors [18][19][20][21]. Increased EAT volume is associated with a lengthened electrocardiogram PR interval [22], suggesting that EAT can interfere with electrical conduction through the heart, modifying the heartbeat.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, the thickness of the EAT is a predictor of fatal and nonfatal coronary events in the general population, regardless of the traditional cardiovascular risk factors [18][19][20][21]. Increased EAT volume is associated with a lengthened electrocardiogram PR interval [22], suggesting that EAT can interfere with electrical conduction through the heart, modifying the heartbeat.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the level of expression of the N-methyl D-aspartate receptor 1 (NMDAR1) and the post-synaptic density-95 (PSD-95) were negatively correlated to the deficient diet alone, and positively correlated to hypoxia. This indicates that the deficiency in B-vitamins affected the hippocampus status in terms of circuit plasticity and that this aspect was maintained during the lifespan, as the Barker theory described for developmental or neonatal events leading to long term positive or negative effects [45,46]. At the same time, the hypoxia-stimulated-mechanism occurring in the same neonatal period could give advantages to receptive circuits such as the hippocampus leading to maintain a long term efficient plasticity even under transient deficiency in B-vitamins.…”
Section: Various Tissue Parameters Attested Of a Rescue Mechanismmentioning
confidence: 81%
“…For several decades, this led to a supplementation program for pregnant women in some countries or food fortification in others [44][45][46]. Considering the brain specificity, which still develops and maturates its circuits after birth, several animal studies have also suggested a prolongation of vitamin status correction to favor a better birth status [47] or brain plasticity and maturation after birth [9,11]. Thus, some brain sub-regions still complete their circuits formation and connectivity based on a so-called hebbian mechanism, even long after birth while young individuals are subjected to internal and environmental factors [11,48].…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms have been proposed to explain observed deleterious effects such as imbalanced proliferation and differentiation of neurons and also brain atrophy leading to cognitive decline and a durable behavioral change in offspring [5][6][7][8][9]. In the context of maternal deficiency in methyl donors, fetal programming is a mechanism described in specific brain functions defects such as locomotion coordination, learning and memory [10,11] . Nevertheless, numerous pathways have been shown to be involved after the deregulation of folate and/or methionine cycles [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%